2018
DOI: 10.1002/nau.23715
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐2 plays an important role in water transportation through the bladder wall in rats

Abstract: The rat urinary bladder absorbs water and salts under the full-filled condition. Aquaporin-2 plays an important role in the transport of water, accompanied by sodium concentration change. We demonstrated a part of the bladder absorption mechanism, which may lead to development of a new method for regulating bladder storage function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…11 We previously reported that AQP-2 plays an important role in the absorption of saline by the rat bladder. 6 In the present study, we found that the AQP-2 expression level increased only in the saline group, suggesting that sodium may be key to inducing AQP-2 expression in rats. Although the reason is unclear, a similar phenomenon was observed in normal human urothelial cell cultures.…”
Section: T a B L Esupporting
confidence: 46%
See 3 more Smart Citations
“…11 We previously reported that AQP-2 plays an important role in the absorption of saline by the rat bladder. 6 In the present study, we found that the AQP-2 expression level increased only in the saline group, suggesting that sodium may be key to inducing AQP-2 expression in rats. Although the reason is unclear, a similar phenomenon was observed in normal human urothelial cell cultures.…”
Section: T a B L Esupporting
confidence: 46%
“…The change in intravesical fluid solution volume was measured 3 hours later as described in our previous study. 6 The intravesical fluid was immediately shipped on ice to Nagahama Life Oriental Yeast Co, Ltd (Shiga, Japan) where concentrations of sodium and chloride and osmotic pressure were measured using the ion-selective electrode method.…”
Section: Change In Intravesical Fluid In Saline and Glucose Group Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that the UBM plays an active role in both solute and fluid reabsorption and is able to modify urine composition . While the underlying biochemical mechanisms have yet to be clarified, it is known that the UBM expresses a variety of receptors and channels including several types of aquaporin water channels and the renal epithelial sodium channel (ENaC), both of which play important roles in vasopressin‐mediated water homeostasis in the kidney . An open question, however, is whether the mammalian UBM also expresses vasopressin receptors and whether expression of vasopressin receptors in the UBM is modified by aging.…”
Section: Introductionmentioning
confidence: 99%